Improving access to health care for chronic hepatitis B among migrant Chinese populations: A systematic mixed methods review of barriers and enablers. Issue 7 (20th February 2017) - Vedio, A.; Liu, E. Z. H.; Lee, A. C. K.; Salway, S.
Summary: Migrant Chinese populations in Western countries have a high prevalence of chronic hepatitis B but often experience poor access to health care and late diagnosis. This systematic review aimed to identify obstacles and supports to timely and appropriate health service use among these populations. Systematic searches resulted in 48 relevant studies published between 1996 and 2015. Data extraction and synthesis were informed by models of healthcare access that highlight the interplay of patient, provider and health system factors. There was strong consistent evidence of low levels of knowledge among patients and community members; but interventions that were primarily focused on increasing knowledge had only modest positive effects on testing and/or vaccination. There was strong consistent evidence that Chinese migrants tend to misunderstand the need for health care for hepatitis B and have low satisfaction with services. Stigma was consistently associated with hepatitis B, and there was weak but consistent evidence of stigma acting as a barrier to care. However, available evidence on the effects of providing culturally appropriate services for hepatitis B on increasing uptake is limited. There was strong consistent evidence that health professionals miss opportunities for testing and vaccination. Practitioner education interventions may be important, but evidence of effectiveness is limited. A simple prompt in patient records for primary care physicians improved the uptake of testing, and a dedicated service increased targeted vaccination coverage for newborns. Further development and more rigorous evaluation of more holistic approaches that address patient, provider and system obstacles are needed.